Implementasi Metode PDCA dalam Pengendalian Kualitas Produk Kerajinan Alat Musik Tradisional: Analisis Kecacatan dan Strategi Perbaikan Berkelanjutan - Ricky Elrangga Andriano; Putu Eka Dewi Karunia Wati (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the application of the Plan-Do-Check-Act (PDCA) method in an SME producing jimbe drums in Blitar, East Java, experiencing defect rate instability ranging from 4.92% to 6.21% during September 2025 – February 2026. Analysis was conducted using seven quality tools, including histogram, Pareto diagram, P-control chart, scatter diagram, and fishbone diagram. Key findings identified four dominant defect types: cracked wood (59.4%), hollow wood (21.2%), cracked paint (10.3%), and torn skin (9.1%), originating from four causal factors: human, material, method, and environment. Corrective actions implemented included standardization of the wood drying process for 2–3 weeks with turning every 4–6 hours, application of anti-pest insecticides post-turning, layered thin-coat painting technique, and controlled skin tension during installation. Post-implementation evaluation showed a significant defect rate reduction from an average of 5.46% to 3.61%, a 34.5% decrease. These results confirm that a PDCA approach integrated with seven quality tools can produce measurable improvements in skill-based handicraft industries.